2007
DOI: 10.1007/s00391-007-0447-1
|View full text |Cite
|
Sign up to set email alerts
|

Misshandlung und Vernachlässigung älterer Menschen durch ambulante Pflegekräfte

Abstract: Although some anecdotal evidence for the phenomenon of abuse and neglect of community-dwelling older care recipients by in-home care services exists, there is an almost complete lack of data on this topic. In order to determine extent and risk factors of abuse and neglect of older care recipients by nurses, we conducted a self-report study among in-home care workers in the German city of Hanover. A total of 503 nurses took part in the study; the response rate was 43.3%. Nearly 40% of all respondents reported h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Also, a survey of 230 educational science and special education students indicated that within their professional group there are a lot of myths and misperceptions about sexual abuse [41]. Education professionals who work with people in need of assistance and/or disabilities also display substantial knowledge gaps and insecurities concerning the topic [5], [7], [10], [21], [39], [43], [51] even though it is assumed that people with disabilities constitute an over proportional amount of sexual abuse victims [14], [15], [16], [23], [24], [27], [34], [43], [44], [46].…”
Section: Need For Professional Trainingmentioning
confidence: 99%
“…Also, a survey of 230 educational science and special education students indicated that within their professional group there are a lot of myths and misperceptions about sexual abuse [41]. Education professionals who work with people in need of assistance and/or disabilities also display substantial knowledge gaps and insecurities concerning the topic [5], [7], [10], [21], [39], [43], [51] even though it is assumed that people with disabilities constitute an over proportional amount of sexual abuse victims [14], [15], [16], [23], [24], [27], [34], [43], [44], [46].…”
Section: Need For Professional Trainingmentioning
confidence: 99%